Wearable antenna gain enhancement using reactive impedance substrate - A.N. Suraya; T. Sabapathy; M. Jusoh; N.H. Ghazali; M.N. Osman; S. Ismail; M. R. Awal (Institute of Advanced Engineering and Science, 2019)
A microstrip patch antenna is designed for a wearable antenna. The performance of microstrip patch antenna loaded with reactive impedance surface (RIS) is described in terms of gain, bandwidth and return loss. The antenna is investigated in two conditions which are conventional microstrip antenna with RIS and without RIS. The designed antenna is also aimed at size reduction therefore it will be suitable for a wearable application. This antenna which is made fully using textile and it is designed for operation in the 2.45 GHz band. The performance of microstrip patch antenna loaded with RIS is described in terms of gain, bandwidth, return loss and radiation pattern. The antenna designed with RIS operates at 2.45 GHz. Bandwidth enhancement is achieved with RIS where the designed antenna can cater frequency from 2.4 GHz to 3 GHz. A gain enhancement is achieved of 20% is achieved compared with the conventional patch antenna. Although the size of the patch is reduced with the introduction of RIS, the overall size of the antenna with the substrate is almost similar to the conventional patch antenna. However, the performance of the antenna is greatly enhanced with the use of RIS.